Pengaruh Efikasi Diri, Pemberian Reward, Fasilitas Belajar, Disiplin Belajar Dan Lingkungan Keluarga Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas X Ips Sma Negeri 4 Payakumbuh - Dwiyanti, Tiari J; Wahyuni, Sri; Eprillison, Vivina (Jurnal Horizon Pendidikan, 2022)
This study aims to analyze the sampling technique using the Stratified Random method. Sampling samples in the study were 86 students. The results of self-efficacy research have a positive and significant effect on learning achievement. coefficients are 0.348241 and 0.355978, respectively. With tcount value of 2.070014 > ttable 1.69552 with significant value 0.0469 < = 0.05 and 2.798753 > ttable 1.68107 with value significant 0.0076 < = 0.05 which means Ha is accepted and Ho is rejected. The provision of rewards has a positive and significant effect on learning achievement. The coefficients are 0.379086 and 0.443925, respectively. Learning facilities have a positive and significant effect on learning achievement. coefficients are 0.150116 and 0.214942, respectively. Learning discipline has a positive and significant effect on learning achievement. coefficients are 0.184940 and 0.128583, respectively. family environment has a positive and significant effect on learning achievement. coefficients are 0.210983 and 0.172287, respectively. self-efficacy, giving rewards, learning facilities, learning discipline and family environment together have a significant effect on student achievement in economics class X Social Sciences SMA Negeri 4 Payakumbuh. Overall the value of Fcount 49.94751 > Ftable 2.33 and significant value 0.000 <α = 0.05, based on the sample group of high parental income, Fcount 11.58369 > Ftable 2.52 and significant value 0.000 <α = 0.05 and based on the sample group the income of parents is low, the value of Fcount is 24,80710> Ftable 2.43 and the significant value is 0.000 <α = 0.05. This means that Ha is accepted and Ho is rejected.